Activation of inert copper for significantly enhanced hydrogen evolution behaviors by trace ruthenium doping. (February 2022) - Huang, Huawei; Jung, Hyeonjung; Li, Shaofeng; Kim, Seongbeen; Han, Jeong Woo; Lee, Jinwoo
Abstract: The application of metallic copper in hydrogen evolution reaction (HER) is severely restricted by its low intrinsic activity due to its surface properties that have large energy barriers for water dissociation and weak binding force to H* . Herein, we report an electronic structure engineering strategy to activate the inert Cu for significantly enhanced HER performance by trace doping of Ru (0.70 wt%). Experiments together with theoretical analysis reveal that the Ru dopants attract electrons from the Cu, resulting in the surface with lower energy barriers for the water dissociation process and optimized binding energy with H* . The synthesized Ru doped Cu only involved overpotentials of 33 and 34 mV to reach 10 mA cm -2 in alkali and acid, respectively, together with excellent long-term stability. This work presents an electronic engineering pathway to adjust the electrocatalysis behaviors of metallic copper. Graphical Abstract: An effective strategy is proposed to activate the inert Cu for significantly enhanced HER performance in both alkaline and acidic conditions by trace doping of Ru. The synthesized Ru doped Cu shows a low overpotential (33 mV) at 10 mA cm -2 in alkaline conditions, being 421 mV lower than that of pure Cu and 18 mV lower than that of commercial Pt/C (Pt: 20 wt%). In acidic conditions, the Ru doped Cu only involves an overpotential of 34 mV at 10 mA cm -2, being also superior to commercial Pt/C. ga1 Highlights: Present an effective strategy to improve catalytic activity of metallic Cu. The Ru doped Cu exhibited excellent HER performance in both acid and alkali. Reveal the role of Ru dopants in the enhanced catalytic activity of Cu.